2009
DOI: 10.11646/zootaxa.2211.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A new frog family (Anura: Terrarana) from South America and an expanded direct-developing clade revealed by molecular phylogeny

Abstract: Three frogs of a new species found in cloud forests on two nearby mountains in Guyana were included in a molecular phylogeny of 17 nuclear and mitochondrial genes (10,739 aligned sites) that revealed that their closest relative is Terrarana (Brachycephalidae, Craugastoridae, Eleutherodactylidae, and Strabomantidae) and their next-closest relative is Hemiphractidae (marsupial frogs). We place these frogs in a new family, genus, and species which is strongly supported as the basal clade within Terrarana: Ceuthom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 44 publications
10
81
2
5
Order By: Relevance
“…Dated molecular phylogenetic studies of frogs and lizards conform to the predictions and timing of these sequential Neogene uplifts (Kok 2013). Moreover, some Pantepui endemics undoubtedly diversified earlier, consistent with the Gondwanan Heritage/Lost World hypotheses, e.g., Terrarana tepui tree frogs in the recently described family Ceuthomantidae (Heinicke et al 2009). Givnish et al (2011) concluded that 'Bromeliads arose in the Guayana Shield ca.…”
Section: Pantepuisupporting
confidence: 56%
See 1 more Smart Citation
“…Dated molecular phylogenetic studies of frogs and lizards conform to the predictions and timing of these sequential Neogene uplifts (Kok 2013). Moreover, some Pantepui endemics undoubtedly diversified earlier, consistent with the Gondwanan Heritage/Lost World hypotheses, e.g., Terrarana tepui tree frogs in the recently described family Ceuthomantidae (Heinicke et al 2009). Givnish et al (2011) concluded that 'Bromeliads arose in the Guayana Shield ca.…”
Section: Pantepuisupporting
confidence: 56%
“…Some recent discoveries include the Terrarana tepui tree frogs of the Pantepui, placed in a new family (Ceuthomantidae - Heinicke et al 2009), the s p o o n -w i n g e d l a c e w i n g s ( N e u r o p t e r a : Nemopteridae: Nemopterinae) of the GCFR and SWAFR (Sole et al 2013). and recent elucidation of the phylogenetic relationships of the monotypic Medusagynaceae trees of Seychelles (Schneider et al 2014).…”
Section: Reduced Dispersability Increased Local Endemism and Common mentioning
confidence: 99%
“…The New World frogs recently classified as the Terrarana comprise five monophyletic clades which are formally recognized as the families Brachycephalidae, Ceuthomantidae, Craugastoridae, Eleutherodactylidae, and Strabomantidae (Hedges et al, 2008;Heinicke et al, 2009). The species of Terrarana share an advanced reproductive mode characterized by terrestrial breeding and direct development of terrestrial eggs that bypass the tadpole stage and hatch into froglets (Lynch and Duellman, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The species of Terrarana share an advanced reproductive mode characterized by terrestrial breeding and direct development of terrestrial eggs that bypass the tadpole stage and hatch into froglets (Lynch and Duellman, 1997). Direct development and the production of small, isolated clutches are life-history traits that contribute to promoting population structuring (Dubois, 2004) and are likely to explain the high diversity of the Terrarana, which currently comprise 1000 species (Hedges et al, 2008;Heinicke et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The format for the description follows Lynch and Duellman (1997), except that the term dentigerous processes of vomers is used instead of vomerine odontophores (Duellman et al 2006), and diagnostic characters are those of Duellman and Lehr (2009). Taxonomic classification follows Hedges et al (2008) and Heinicke et al (2009), except that we followed Pyron and Wiens (2011) for family placement, and Padial et al (2014) for names of Pristimantis species groups. Specimens were fixed in 96% ethanol and stored in 70% ethanol.…”
Section: Methodsmentioning
confidence: 99%